Fire Behaviour of Treated Insulation Fibreboards and Predictions of its Future Development Based on Natural Aging Simulation - Osvaldová, Linda Makovická; Mitrenga, Patrik; Jancík, Juraj; Titko, Michal; Efhamisisi, Davood; Košútová, Katarína (Frontiers in Materials, 2022)
The aim of this research work was to evaluate the effect of long-term aging on the combustibility of low-density insulation fibreboards (IFs) treated with a water-soluble flame retardant (FR) based on inorganic salts. Both natural and accelerated aging simulations were conducted. The accelerated aging simulation was performed using climate chambers. The FR efficiency was evaluated by the mass loss rate of the tested specimen. As expected, the FR formulation used significantly enhanced the fire properties of the boards, reaching maximum efficiency six months after its application onto the fibreboards. Markedly, after four years the efficiency of the investigated FR additive was considerably decreased with weight loss values comparable with the values of the untreated samples. The development of accurate datasets on the thermal behaviour of IFs is critical for their proper utilisation in building and construction applications.